Health Development of the Dalung Traditional Village Credit Institution in Badung Regency, Bali Province - Purantara, Anak Agung Gede (JURNAL MANAJEMEN AGRIBISNIS; Vol 12 No 1 (2024): Jurnal Manajemen Agribisnis, 2024)
Village Credit Institutions (LPD) play a very large role in informal sector businesses. This indicates the added value of LPD which makes its customers, especially small and micro entrepreneurs, prefer LPD over formal financial institutions as back up finance for their business. This added value then makes LPDs in Bali superior to existing formal financial institutions. The Dalung Traditional Village LPD in Badung Regency is one of the LPDs that still exists during the COVID-19 pandemic. This research uses secondary data for three years (2020-2023). The method used is the CAMEL method (Capital, Asset quality, Management, Earnings and Liquidity). The research results show that the health level of the Dalung Traditional Village LPD is classified as healthy.